A Sociolinguistic Analysis of Slang Words Used in Pulp Fiction Movie Directed By Quentin Tarantino - Ryanda, Muhammad Abdil Ghiffari; Pratama, Rizky Mirani Desi (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
This research was conducted by analysing slang language in the script of "Pulp Fiction" by Quentin Tarantino. The study ac imed to identify and analyse the types, meanings, and functions of slang used in the film's script. The primary source of this research is the script of "Pulp Fiction." The writer employed a descriptive qualitative method, reviewing and identifying slang dialogues using English translations, then capturing screenshots of important dialogues relevant to the chosen title. The slang words found in the "Pulp Fiction" script are categorized into two types according to Chapman's theory (1988): Primary Slang and Secondary Slang. In this study, there are 19 slang words classified into these two types, each found in various sentences throughout the "Pulp Fiction" script. The dominant type of slang is Primary Slang, with the most frequently used word being ain't, which appears 47 times. In contrast, the word O.D.ing in Secondary Slang is used only 3 times.